Analysis of the influence of communication, leadership, and work teams on nurse discipline - Lumastari Ajeng Wijayanti; Dewi Nurhanifah; Nordianiwati Nordianiwati; Yolanda Anastasia Sihombing (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: The availability of quality health services for the community must receive attention from the government as one of the efforts to develop the health sector. Disappointing evidence regarding improvement in nurses' safe and quality care elevates the need to broaden our knowledge regarding the factors that enhance constant learning in nursing teams. Objective: Analyzes the effect of communication, leadership, and teamwork on nurse discipline. Methods: This quantitative research uses an analytical observational approach and a cross-sectional research design. With the analysis of the data, a linear regression test. The sample was selected using the cluster random sampling method with 36 respondents. Result: This shows the results of a linear regression test with a communication value of p = 0.024, a leadership p = 0.057, and a work team value of p = 0.004, so it can be supposed that there is an influence between the effectiveness of the work team and nurse discipline. So, it can be concluded that the point of communication and the effectiveness of the work team affect the discipline of nurses. Conclusion: the effect of the level of communication effectiveness and the effectiveness of the work team on the discipline of nurses. The story of the effectiveness of nurses can be increased by regulating the flow of information by sending authorized delegates. They are utilizing feedback to maintain organizational communication effectiveness by providing nurses with orientation, direction, and supervision.